Perceptions of parasitic diseases in childhood: An experience in Primary Health Care (Research, Society and Development, 2025)
Introduction: Knowledge about the epidemiology of parasitic diseases, especially in childhood, is fundamental for qualified action in Primary Health Care. Objective: The main goal of this study was to conduct a cross-sectional observational study in Basic Health Units on knowledge about parasitic diseases in childhood among health professionals and community members assisted in primary care. Method: This is a descriptive qualitative study conducted in three Basic Health Units (BHUs) located in the municipality of Ponta Grossa, Paraná. Data collection was conducted between February and April 2024, using proprietary questionnaires structured with objective questions from an interdisciplinary perspective. Results: Failures in the clinical and therapeutic management of parasitic diseases were identified, attributed to gaps in knowledge on the subject, both on the part of health professionals and the community. Conclusion: Given this, there is an urgent need for community education campaigns aimed at the prevention of enteroparasitosis, as well as the continuous training of teams working in Primary Health Care.